KARAKTERISTIK BIO-OIL DARI LIMBAH INDUSTRI HASIL HUTAN MENGGUNAKAN PIROLISIS CEPAT - Santiyo Wibowo (Jurnal Penelitian Hasil Hutan, 2016)
Petroleum consumption is increasing, while the supply is continuously depleted. Currently, the alternative biofuel such as bioethanol, biodiesel and bio-oil have been developing from various natural sources, including forest product’s waste. This paper studies the characteristic of bio-oil made of wastes from forest industries by fast pyrolysis process. Mahogany wood powder, bark and paper sludge were heated in the temperatures of 400°C, 450°C, 500°C, and 550°C to produce bio-oil. Results show that bio-oil can be produced from all three materials studied. Mahogany wood powder which was heated at 550°C produces the highest liquid yield of 25%, yields of bio-oil is 5%, phenol 3.66%, pH 2.98, specific gravity 1.092 g/cm³, heating value 9.28 MJ/kg. The fast pyrolysis process produces bio-oil which is predominantly composed of acetic acid and phenols.